2022
DOI: 10.3390/jcm11133835
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and/or Anti-Fibrotic Treatment of MPO-ANCA-Positive Interstitial Lung Disease: A Short Review

Abstract: The presence of a lung lesion is common in microscopic polyangiitis (MPA), and interstitial lung disease (ILD) can lead to a poor prognosis. Although myeloperoxidase antineutrophil cytoplasmic antibodies (MPO-ANCA) are often present in patients with MPA, patients with ILD and MPO-ANCA positivity but without other manifestations of systemic vasculitis have also been reported. Therefore, the possible association between MPO-ANCA, MPA, and idiopathic ILD remains unclear. This problematic matter has influenced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Thus, if we could intervene more quickly by administering an anti-brotic agent early to patients with worsened pulmonary function, the patients with PF-ILD or PPF in the present study who underwent TBLC might have bene tted from early introduction of an anti-brotic agent. Expansion of brotic change in patients with both a radiological and pathological UIP pattern can lead to a high risk of PPF or PF-ILD, which means a poorer prognosis for any of the ILDs [5,23,24]. Therefore, the descriptive research undertaken in the present study suggested that additional TBLC pathological information can contribute to early medical intervention particular in terms of anti-brotic agent administration in clinical practice, although a comparative study to assess this might be di cult.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, if we could intervene more quickly by administering an anti-brotic agent early to patients with worsened pulmonary function, the patients with PF-ILD or PPF in the present study who underwent TBLC might have bene tted from early introduction of an anti-brotic agent. Expansion of brotic change in patients with both a radiological and pathological UIP pattern can lead to a high risk of PPF or PF-ILD, which means a poorer prognosis for any of the ILDs [5,23,24]. Therefore, the descriptive research undertaken in the present study suggested that additional TBLC pathological information can contribute to early medical intervention particular in terms of anti-brotic agent administration in clinical practice, although a comparative study to assess this might be di cult.…”
Section: Discussionmentioning
confidence: 80%
“…Avacopan might hold promise if MPO-ANCA ILD is complement-mediated. Empirical management approach to patients with MPO-ANCA ILD has been proposed [ 8 , 77 , 78 ] and there are no guidelines, apart from patients with overt MPA [ 79 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if we could intervene more quickly by administering an antifibrotic agent early to patients with worsened pulmonary function, the patients with PF‐ILD or PPF in the present study who underwent TBLC might have benefitted from early introduction of an antifibrotic agent. Expansion of fibrotic change in patients with both a radiological and pathological UIP pattern can lead to a high risk of PPF or PF‐ILD, which means a poorer prognosis for any of the ILDs [ 5 , 24 , 25 ]. Therefore, the descriptive research undertaken in the present study suggested that additional pathological information obtained from TBLC can contribute to early medical intervention particular in terms of antifibrotic agent administration in clinical practice, although a comparative study to assess this might be difficult.…”
Section: Discussionmentioning
confidence: 99%